Supplementum epigraphicum mediterraneum - Best, J. G. P. (1982)
Cretan pictographic signs traced in part to cuneiform origin; the goddess Aššara in Haghia Triada Linear A tablets; the language of Linear A documents and Cretan pictographic documents is Semitic.